Gel-forming Mucins in Oviductus Ranae Contribute to Swelling Capacity by iTRAQ Proteomics Analysis - Zhang, He; Zhang, Yuyao; Yang, Chunhui; Su, Wenjie; Pan, Daian; Zhao, Daqing; Jing, Li; Qi, Bin (Indian Journal of Pharmaceutical Education and Research, 2021)
Introduction: Oviductus Ranae (OR) is the dried oviduct of female Rana temporaria chensinensis David, which is one of the best-known and highly valued oriental foods and medicines in China. OR has a unique physiological phenomenon that is high swelling capacity. Objectives: We aimed to study which components are associated with high swelling capacity in OR. Materials and Methods: isobaric tags for relative and absolute quantification (iTRAQ) proteomic methods were used to identify differentially expressed proteins between the OR and three counterfeit oviducts, including Rana nigromaculata, Bufo bufogargarizans and Rana catesbeiana to explore the mechanism of swelling capacity. Results: We found that a total of 1220 proteins were identified from 2149 unique peptide sequences. Comparing with three counterfeit oviducts, 11 differentially expressed proteins were identified in OR, including 9 up-regulated proteins, such as mucins (MUC2, MUC5AC, MUC5AC-like, MUC5B), PREDICTED: a-kinase anchor protein 13-like (AKAP13-like), PREDICTED: IgGFc-binding protein (FcγBP), PREDICTED: IgGFc-binding protein-like (FcγBP-like), et al. and 2 down-regulated proteins. Bioinformatics results found that these up-regulated proteins were involved in biological processes, including metabolic process, cellular process, responses to stimulus and biological regulation. Conclusion: Mucins, AKAP13-like, FcγBP and FcγBP-like may act as a positive regulator for the innate immune response in oviduct of Chinese brown frog and exceptional swelling capacity of OR is closely related to gel-forming mucins. Taken together, our results provide the basis for further understanding of the unique physiological phenomenon of OR.
Keywords: Oviductus Ranae; Swelling capacity; Gel-forming mucins; Counterfeit oviducts; Differentially expressed proteins